A Spanish poet at the court in Vienna: Weltanschauung and anti-Petrarchism in Cristóbal de Castillejo - Martínez Navarro, María del Rosario (Studia Europaea Gnesnensia, 2012)
The figure of the humanist Cristóbal de Castillejo (Ciudad Rodrigo, 1490- Vienna, 1550) plays a fundamental role in 16th centuryEurope, embodied by emperor Charles V. The most significant aspect in the poet’s biography, a fact borne out by his famous works, was the early association with the court of one of the most charismatic and prominent figures of the then Central Europe, the archduke ofAustria and the ruler ofBohemia andHungary, Ferdinand, the emperor’s brother. First as a page, when Ferdinand was only the Spanish infant, and later as a royal secretary inVienna, he participated in king’s travels as well as important political and literary events. This privileged position found its reflection not only in the official accounts, but also in Cristóbal de Castillejo’s work. The twenty five years spent at the court inVienna have their testimony in the highly valuable epistolary anthology entitled ”El emperador Carlos V y su corte según las cartas de don Martín de Salina”.